Resistance of Concrete Masonry Units and Prisms in Costa Rica - Abarca Jiménez, Andrés (2025)
The Technical Standards Institute of Costa Rica (INTECO) was created in 1987 in response to a Costa Rican need for technical standardization. INTECO has greatly evolved over the years developing a very wide range of regulations with around 30 technical committees and more than 500 published standards. Within these committees is the "CTN 04 Bituminous Mixtures and Asphalts Binders” which belongs to the category of Asphalt Mixtures, developed in 2004 thanks to the efforts of LanammeUCR. This document includes a summary of each INTECO standard related to Asphalt Mixes, with illustrative images of equipment and recommendations by professionals of LanammeUCR to ensure the correct application of these processes. This summary also includes three comparative tables with the most important differences of equipment, procedures and precision and bias between the latest AASHTO and ASTM bituminous mixtures standards and their equivalent to INTECO standard. These methods have not being updated in Costa Rica in more than seven years, so the former members of the technical committee as well as anyone in the field are invited to be part of a new team to not only update these rules but also create new ones.